Trade in times of uncertainty - Anna Matzner; Birgit Meyer; Harald Oberhofer (Austrian Institute of Economic Research (WIFO), 2023)
This paper analyses the direct and indirect trade volume and trade cost effects of uncertainty on international trade and economic welfare using a structural gravity framework for a panel of 97 developed and developing countries from 2000 to 2018. Our results suggest that an increase in unilateral uncertainty affects average trade costs in a heterogeneous manner, depending on whether the uncertainty originates from the importing or exporting country. Moreover, using a cross-sectional gravity approach, we show that an uncertainty shock directly reduces cross-border trade flows. The paper illustrates the suitability of the proposed modeling approach by means of two counterfactual scenario analyses in which we calculate the general equilibrium trade and welfare effects of uncertainty induced by the unexpected outcome of the Brexit referendum in 2016 and the outbreak of the COVID-19 pandemic in 2020.
Keywords: F13; F14; F42; E60; 330; International Trade; Trade Costs; Gravity; Uncertainty; Counterfactual Scenario Analysis; Brexit; COVID-19